Humankapital in der Transformation - Das Beispiel der neuen Länder - Ralf Müller (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2000)
– The human capital of a nation is highly correlated to its productivity. Thus, differences in human capital may be seen as one factor determining the productivity gap between East and West Germany. However, a disadvantage of East Germany with regard to hu-man capital only shows up as long as it concerns skills that are built up on the job, i.e., by learning by doing; even more, this disadvantage has been decreasing in the 1990's. In contrast, as long as it concerns skills that have been acquired through formal education, East Germany has a high level of human capital in comparison to West Germany. In general, the problem of East Germany's human capital proves to be rather demand-sided. It may be due to East Germany's low skill-intensive industry structure.
urn:nbn:de:gbv:3:2-18562
Keywords: I21; J24; 330; East Germany; education; human capital; productivity; transformation; Humankapital; Systemtransformation; Bildungsinvestition; Arbeitsproduktivität; Neue Bundesländer